The Treasure of the Bucoleon - Smith, Arthur D. Howden (Arthur Douglas Howden), 1887-1945 (Salt Lake City, UT : Project Gutenberg, 2020)
"The Treasure of the Bucoleon" by Arthur D. Howden Smith is a novel written in the early 20th century. The story revolves around Hugh Chesby, who receives a mysterious cable from his uncle hinting at an important treasure linked to their family's history in Constantinople. Along with his friends, including his cousin Betty and their mutual acquaintance, the gypsy violinist Nikka Zaranko, Hugh becomes embroiled in a thrilling adventure that intertwines danger, legacy, and the pursuit of a long-lost fortune. The opening of the novel introduces Hugh and his circle as they discuss the lore of a treasure believed to be hidden in Constantinople, known as the Treasure of the Bucoleon. Through their conversation, it is revealed that Hugh's uncle has been obsessed with finding this treasure, and his latest correspondence suggests that he has made a significant discovery. However, shortly after arriving in New York, Hugh's uncle is brutally attacked, leaving behind more questions than answers. The initial chapter sets the stage for a tense adventure filled with historical intrigue, personal stakes, and the shadow of danger lurking as they embark on the quest to uncover the treasure$1 (Bs secrets. (This is an automatically generated summary.)s
Release date is 2020-10-01
Produced by Al Haines
Keywords: Adventure stories; Treasure troves -- Fiction; Constantinople -- Fiction